HUBUNGAN PEMILIHAN BINGKAI KACAMATA YANG TIDAK TEPAT DENGAN KELUHAN ASTHENOPIA PADA PENGGUNA KACAMATA FLATTOP - Nugraha, Opep; Rizki Abdilah, Bunyamin; Budiana, Wahyu (Akademi Refraksi Optisi dan Optometry Gapopin, 2025)
Flat-top bifocal glasses have a near segment located at the bottom of the lens. Inappropriate frame selection can cause suboptimal positioning of this segment, forcing users to adopt unnatural head postures when reading, thus potentially triggering asthenopia. This study aims to analyze the relationship between the accuracy of eyeglass frame selection and asthenopia complaints in flat-top glasses users. An analytical observational study with a cross-sectional design was conducted on 82 flat-top glasses users selected by consecutive sampling. Data were collected through structured interviews using an asthenopia complaint questionnaire and physical examination by an optometrist to assess frame accuracy based on parameters: near segment height, pantoscopic angle, and vertex distance. Data were analyzed using the Chi-Square test. A total of 65.9% of respondents (54 people) experienced asthenopia complaints. The proportion of inappropriate frame selection was significantly higher in the group with asthenopia (83.3%) compared to the group without asthenopia (21.4%) (p < 0.001). The most frequently inaccurate frame parameter was inappropriate near segment height (p=0.001).There is a significant relationship between inappropriate eyeglass frame selection and asthenopia complaints in flat-top glasses users. The accuracy of frame fitting, especially the near segment height, is a critical factor that must be considered.